Description of the larva of Paraphlebia zoe Selys in Hagen, 1861(Odonata: Megapodagrionidae) - Novelo-Gutiérrez, Rodolfo (Zootaxa, 2008)
The larva of Paraphlebia zoe is described, this being the first for the genus Paraphlebia. It is compared to all other known neotropical megapodagrionid larvae from which it can be distinguished by following combination of characters: antenna shorter than length of head; second antennomere the longest; prementum slightly wider than long; male gonapophyses absent; gills strongly inflated with a thick caudal filament. The larva inhabits seepages.